Monseñor Juan Larrea Holguín: Ícono del Derecho ecuatoriano - Pablo Zambrano Albuja (Universidad Hemisferios, 2020)
These lines collect a bibliographic review of the most prolific Ecuadorian jurist, Monsignor Juan Larrea Holguín, exposed on the occasion of the seventh edition of the Juan Larrea Holguín International Award. Specifically, it includes his humanistic facet, his service to God and law, and especially his contribution to the national and international law academy.